Probiotics, Pre-biotics and Synbiotics in the Treatment of Pre-diabetes: A Systematic Review of Randomized Controlled Trials - Wang, Xian; Yang, Jiao; Qiu, Xianliang; Wen, Qing; Liu, Min; Zhou, Dongqi; Chen, Qiu (Frontiers in Public Health, 2021)
Objectives: This study aimed to review the data from randomized controlled trials (RCTs) and identify evidence for microbiota's role and use of probiotics, pre-biotics, or synbiotics in pre-diabetes. Methods: RCTs of pro-, pre-, synbiotics for the treatment of pre-diabetes population will be summarized. We searched for EMBASE, MEDLINE, Web of Science, Cochrane Central, Clinical Trials (ClinicalTrials.gov) from inception to February 2021. Results: The gut microbiota influences host metabolic disorders via the modulation of metabolites, including short-chain fatty acids (SCFAs), the endotoxin lipopolysaccharides (LPS), bile acids (BA) and trimethylamine N-oxide (TMAO), as well as mediating the interaction between the gastrointestinal system and other organs. Due to the limited sources of studies, inconsistent outcomes between included studies. Probiotics can decrease glycated hemoglobin (HbA1c) and have the potential to improve post-load glucose levels. The supplementation of probiotics can suppress the rise of blood cholesterol, but the improvement cannot be verified. Pre-biotics are failed to show an evident improvement in glycemic control, but their use caused the changes in the composition of gut microbiota. A combination of probiotics and pre-biotics in the synbiotics supplementation is more effective than probiotics alone in glycemic control. Conclusion: In the current studies using probiotics, pre-biotics or synbiotics for the treatment of pre-diabetes, the benefits of modulating the abundance of gut microbiota were partially demonstrated. However, there is insufficient evidence to show significant benefits on glucose metabolism, lipid metabolism and body composition.